ESTUDIO FITOSOCIOLÓGICO DE LAS COMUNIDADES DE MALEZAS ASOCIADAS AL CULTIVO DE Zea mays (MAÍZ) EN VARIAS ZONAS DEL TRÓPICO ECUATORIANO - Bermello Sanchez, Shirley Viviana (2023)
The research focused on carrying out a phytosociological study of weed communities associated with Zea mays (maíz) crops in several areas of the Ecuadorian tropics specifically in the cantons of Mocache, Ventanas and Balzar. Weeds, known as weeds, represent a significant challenge to growing corn due to their competition for resources such as sunlight, water, nutrients and growing space. This phenomenon leads to reductions in crop yield and increases harvest costs. The results of the research revealed that the Poaceae family was identified as the most abundant.